P006 Rituximab biosimilar switching shows non-inferior outcomes in routine clinical practice. (23rd April 2022) - Bilan, Jimmy; Chew, Xin; Perry, Martin E
Abstract: Background/Aims: Biosimilar biologic therapy has been widely implemented in recent years. However, little data exists outwith clinical trials to confirm patient response to therapy and any safety signal following switch from originator products or between biosimilars. This study reviewed all rheumatoid arthritis patients prescribed biosimilar rituximab in a 'real world' clinical practice setting to a certain clinical response following switching. Methods: Retrospective review of clinical data from medical record was undertaken across three hospital sites in the UK. Patients were identified from biologic database and infusion facility records. Basic demographics were collected. The current biosimilar brand of rituximab, previous brands including originator were also collected and previous record of biologic and steroid therapy. The DAS-28 ESR was recorded pre- and post-biosimilar switch along with any note of infusion reactions. Results: The database screening of 925 patients on biologic therapy identified 64 patients with rheumatoid arthritis taking rituximab biosimilar therapy. 48 female and 16 male patients with mean disease duration of 7.7 years were identified. 78% of patients were seropositive and all were on 6-monthly pulse infusions of 1g rituximab, 2 weeks apart. 34 (52%) patients were also taking methotrexate, (mean dose of 15mg/wk). Nine patients (14%) were taking concurrent oral prednisolone. Mean current DAS-28 ESR was 3.23. At biosimilar initiation DAS-28 was 4.00 (19% fall, non-significant). There were 14 adverse events, of which 11 were infusion-related reactions, six of which were for truxima, the remainder were with mabthera and rixathon. No anaphylaxis was recorded, although one patient had a hypersensitivity reaction. 38 (59%) patients had rituximab as first biologic. Conclusion: This 'real-life' clinical review found similar clinical efficacy of rituximab biosimilar to originator product based on the DAS-28 ESR score. There were no notable safety or infusion differences. Disclosure: J. Bilan: None. X. Chew: None. M.E. Perry: Honoraria; Lilly, Celltrion, Gilead, Abbvie, Biogen, Jaansen.